2005
DOI: 10.1111/j.1365-2044.2005.04296.x
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac output measurement by pulse dye densitometry in cardiac surgery

Abstract: SummaryThe aim of this study was to compare the accuracy of pulse dye densitometry with that of bolus thermodilution cardiac output measurement in patients before and after elective coronary artery bypass grafting. Twenty-eight patients were studied. Agreement between mean thermodilution and pulse dye densitometry cardiac output values was assessed by Bland-Altman analysis. [2.0-7.2] l.min )1 for pulse dye densitometry using indocyanine green 20 mg. Mean bias was + 0.566 l.min )1 , the limits of agreement were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 22 publications
0
28
0
Order By: Relevance
“…It was also clinically utilized for testing the liver function because the dye is extracted from the body by methabolisation in the liver [4][5][6][7]. ICG-tracking method was also proposed and tested as a tool for estimation of the blood circulation parameters in humans [8][9][10][11][12][13][14]. Considering these applications of ICG, the toxicity tests were carried out on retinal cell cultures [15] and retina model ex-vivo [16] showing cytotoxic effects in a dose, patients and time-dependent manner.…”
Section: Introductionmentioning
confidence: 99%
“…It was also clinically utilized for testing the liver function because the dye is extracted from the body by methabolisation in the liver [4][5][6][7]. ICG-tracking method was also proposed and tested as a tool for estimation of the blood circulation parameters in humans [8][9][10][11][12][13][14]. Considering these applications of ICG, the toxicity tests were carried out on retinal cell cultures [15] and retina model ex-vivo [16] showing cytotoxic effects in a dose, patients and time-dependent manner.…”
Section: Introductionmentioning
confidence: 99%
“…The technique is subject to interference from multiple sources -vasoconstriction, poor peripheral circulation, insterstitial oedema, movement or ambient light artefacts and as a result validation studies have only shown moderate agreement with thermodilution techniques. 108, 109 We could find only one study using this technique in pregnancy performed by Ueyama et al 110 They attempted to clarify the effects of volume preload with either crystalloid or colloid solutions in parturients undergoing spinal anaesthesia for caesarean section and measured CO with non-invasive pulse spectrophotometry using idocyanine green blood concentrations. This study used a similar methodology to Tamilselvan et al with the suprasternal Doppler albeit less elegantly.…”
Section: Pulsed Dye Densitometrymentioning
confidence: 98%
“…[14][15][16] In PDD, an additional wavelength of light is used to match the extinction peak for a particular dye for comparison to an IR wavelength outside of the extinction spectrum for that dye. The ratio of the extinction at these two wavelengths gives information about the ratio of dye to hemoglobin present in the blood.…”
Section: Introductionmentioning
confidence: 99%